CONTROLLERS FOR HANDLING THREE PHASE GRID FAULTS IN VOLTAGE SOURCE CONVERTER BASED HVDC TRANSMISSION SYSTEMS - Dr. S.Prakash,Dr.R.Dhanasekaran, D.A.Suresh,P.Ramesh (International Journal of Advanced Science and Technology, 2020)
Integrating asynchronous AC generators to AC grid is a challenging task. For example if there are AC generators of 50 Hz and 60 Hz frequency, synchronizing them to a common grid not possible. Such issues can be addressed using High Voltage Direct Current (HVDC) transmission which connects asynchronous sources at either ends. In Voltage Source Converter (VSC) based HVDC transmission both real and reactive power transmitted can be controlled where as in conventional line commutated converter based HVDC transmission system, only the real power transmitted was controlled. There may be chances of grid faults in both the ends. The typical faults are single line to ground fault, double line to ground fault ant three phase fault. The faults occurring in one grid side should not affect the other side grid. To handle such faults, the voltage sources converters should be controlled to regulate the power transmitted through the line such a way that the fault in one grid will not affect the other grid parameters. This paper represents a control structure for VSC based HVDC transmission system which will handle three phase fault in both the grids.